Sharing the magic circle with spatially inclusive games - Champion, Erik; Jacobson, J. (2008)
Four types of interactive environments explored ways to extend gaming beyond the limitations of the personal computer's conventional desktop interface. These projects aimed to challenge John Huizinga's notion of a "magic circle", the imaginary boundaries of the fantasy world that players of a game occupy. By expanding and diffusing the "magic circle", we believe we can more richly and thematically immerse the player, and more directly involve the audience. The projects were: surround projection environments (using a spherical mirror and warping code); surround projection in custom-built surround spaces with thematically designed tangible interfaces; arcade-style games; and bodily aware-games (using indirect and subconscious biofeedback that changes the music, "boss" monsters, and shaders). The working prototypes were considered successful by the students' peers and by visitors, but were also successful in engaging the students with the interface possibilities and interaction issues of unconventional game design. We also intend to further develop and provide some of these tools to the wider academic community.